Application of biotechnology: evaluation of improved-quality planting materials for forest plantation species / Ahmad Zuhaidi Yahya …[et al.] - Yahya, Ahmad Zuhaidi; Ab Ghani, Ab Rasip; M. Shariff, Ahmad Fauzi; Koter, Rosdi (2006)
Improved planting materials of Dyera costulata, Endospermum malaccense and Acacia hybrid were first introduced and trial-planted by the Silviculture Unit, Forest Research Institute Malaysia in 1998. The growth using improved materials performed well ill the open and has an average volume production of 37.58, 50.46 and 95.79 m3 ha-1 respectively. These species is categorized as fast growing hardwood and planned for specific objectives depending on wood quality. This paper highlights the potential of each species for future large-scale plantation.